Knowledge and Attitude Towards Organ Donation Among the Staff of an Islamic Tertiary Education Centre in Malaysia - Nazefah Abdul Hamid (Springer, 2024)
Islamic scholars have been discussing organ donation issues since it is not specifically mentioned in Al-Quran and Hadith. Organ donation is permissible in Islam because it fulfils the requirement in the preservation of human life, which is one of the five objectives in maqasid syariah. It is believed that the awareness to donate organs is based on good knowledge and attitude among members of the public. Hence, this study aims to determine knowledge and attitude towards organ donation among Universiti Sains Islam Malaysia’s (USIM) staff. A cross-sectional study using systematic random sampling was conducted. A total of 103 USIM staff responded to the self-administered and validated questionnaire. The respondents comprised of 32 (30.8 %) academic, 11 (10.6 %) administrative and 60 (57.7 %) support staff. A quarter of the respondents were Diploma holders (26 %) followed by Masters’ degree holders (22.1 %). The total scores for knowledge and attitude were 7.68 (SD 1.615) and 31.89 (SD 4.845), respectively. There was a significant correlation between total knowledge and total attitude score (p = 0.038, r = 0.204). There was no significant mean difference in the knowledge and attitude scores of male and female staff. The mean knowledge showed positive correlation with age (p = 0.042, r = 0.200). As a conclusion, the knowledge and attitude towards organ donation were good among the staff. However, aggressive educational campaigns with Islamic input highlighting the concept of daruriyyah and maqasid syariah are needed to promote and create awareness regarding organ donation in Malaysia.